(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Malaria is a serious illness resulted from parasites that are communicated to people through the bites of infected female Anopheles mosquitoes. Malaria is still in a worrying trend, particularly in tropical and subtropical climates although it is curable and preventable. In spite of a noteworthy abetment in incidence and death rates caused by malaria, even in 2017, a big number of people (219 million) have been affected by it along with 435 thousand confirmed death cases. Though a lot of synthetic drugs have been commercialized to treat malaria, those are compromised with some serious side effects. On the contrary, plant sources are always getting a big focus to develop novel and effective therapeutics in the treatment of different ailments i.e. quinine and artemisinin to treat malarial complications. The usage of herbal plants against malaria has also a very ancient root. Several families of plant species have showed potential antimalarial activities in previous research works. In this review work, families of these plants have been compiled so that prospective researchers can find a hint to discover more effective and safer plant-derived therapeutic options against malaria. Bangladesh Pharmaceutical Journal 24(2): 180-193, 2021